The Strategic Role of IT Capability in Police Organizational Transformation: Toward Smart Policing - Tono Listianto (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Digital transformation not only provides positive convenience for the community, but also has implications for the declining level of security. Therefore, the Indonesian National Police (Polri) is required to transform by strengthening resources to meet public demands for effective and efficient security and protection, including security and protection of digital space that is carried out with precision, effectiveness, and efficiency. This study aims to explore the strategic role of information technology capabilities in the transformation of police organizations as an implementation of Smart Policing at the sectoral level. This research uses a qualitative approach and is analyzed using empirical study techniques. Empirical research is research based on the observation and measurement of social phenomena. One of the main insights from this study is that IT capabilities act as a supporter of dynamic capabilities. Dynamic capabilities refer to an organization's ability to integrate, build, and reconfigure internal and external resources to respond to environmental changes. Organizations that invest in developing strong IT capabilities will be better prepared to integrate new technologies, support knowledge sharing, and facilitate collaborative innovation processes. These capabilities increase organizational agility and enable organizations to respond quickly to emerging opportunities and challenges. At the same time, strategic management of IT resources ensures that technology initiatives align with broader organizational goals and deliver measurable organizational value. These findings suggest that organizations seeking to strengthen innovation performance should prioritize policies related to developing comprehensive IT capabilities, combining technology infrastructure, skilled personnel, and effective governance structures. In doing so, police organizations can create an environment that encourages creativity, experimentation, and continuous learning.